1993
DOI: 10.1002/bmc.1130070108
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of salbutamol and terbutaline at overdose levels in human plasma by high performance liquid chromatography with electrochemical detection

Abstract: A multidimensional column chromatographic method involving electrochemical detection using a carbon fibre microelectrode flow cell was optimized and successfully applied to the simultaneous determination of salbutamol and terbutaline in plasma at overdose levels. This method performs, in a single step, an efficient extraction and clean-up of salbutamol and terbutaline from human plasma. The calibration graphs over three days were linear over the calibration range 20-100 ng/mL plasma with a limit of detection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…neither plasma nor urine, Fenoterol was determined in plasma after derivatisation with HPLC-fluorescence [9] to a LLOQ of 376 pg/mL or HPLC-MS/MS to a LLOQ of 2.5 ng/mL, Salbutamol (Albuterol) was determined with HPLC-MS [10] with a LLOQ of 100 pg/mL or GC-MS [11] with a LLOQ of 2 ng/mL or HPLC-fluorescence [12,13] with a LLOQ of 50 pg/mL, Terbutaline was determined with HPLC-MS/MS [14] with a LLOQ of 1 ng/mL or HPLC electrochemical detection [15] with a LLOQ of 0.8 ng/mL. All published methods regarding Formoterol related substances have a LLOQ between 50 pg/mL and 5 ng/mL in plasma or urine except Formoterol itself for which a LLOQ from 4 to 20 pg/mL was achieved with very time consuming methods [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…neither plasma nor urine, Fenoterol was determined in plasma after derivatisation with HPLC-fluorescence [9] to a LLOQ of 376 pg/mL or HPLC-MS/MS to a LLOQ of 2.5 ng/mL, Salbutamol (Albuterol) was determined with HPLC-MS [10] with a LLOQ of 100 pg/mL or GC-MS [11] with a LLOQ of 2 ng/mL or HPLC-fluorescence [12,13] with a LLOQ of 50 pg/mL, Terbutaline was determined with HPLC-MS/MS [14] with a LLOQ of 1 ng/mL or HPLC electrochemical detection [15] with a LLOQ of 0.8 ng/mL. All published methods regarding Formoterol related substances have a LLOQ between 50 pg/mL and 5 ng/mL in plasma or urine except Formoterol itself for which a LLOQ from 4 to 20 pg/mL was achieved with very time consuming methods [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 A literature survey revealed that various analytical methods have been reported for the estimation of TBS; they include UV spectroscopy, 3,4 voltammetry, 5,6 capillary electrophoresis, [7][8][9] chemiluminescence, [10][11][12] high performance liquid chromatography (HPLC), 1,13,14 HPLC-fluorescence detection, 15 HPLC-electrochemical detection, 16,17 HPLCchemiluminescence detection, 18 RP-liquid chromatography, 19 LC-electrochemical detection, 20 column-switching LC, 21 LC-tandem mass spectrometry, 22,23 and high-resolution GC-mass spectrometry analysis. 24 For TBS pharmacokinetic studies, the most useful analytical method is GC-mass spectrometry.…”
Section: Terbutaline Sulfate (Tbs); β-[(Tert-butylamino)methyl]-35-mentioning
confidence: 99%
“…7,8 Both normal phase, 9 but predominantly reversed phase, high performance liquid chromatography (HPLC) methods have been reported for salbutamol using either fluorescence 9,10,11,12 or electrochemical detection. 13,14,15 These HPLC methods have employed either liquid-liquid 11,13 or solid phase extraction (SPE) 9,12,15 procedures and the use of column switching technology has also been reported. 14 The main drawback of these HPLC methods has been a lack of sensitivity.…”
mentioning
confidence: 99%
“…13,14,15 These HPLC methods have employed either liquid-liquid 11,13 or solid phase extraction (SPE) 9,12,15 procedures and the use of column switching technology has also been reported. 14 The main drawback of these HPLC methods has been a lack of sensitivity. With lower limits of quantification (LLoQ) in the low ng/mL range, they have only been suitable for defining the pharmacokinetics of salbutamol after oral and intravenous dosing.…”
mentioning
confidence: 99%